Analisis Amenitas dan Daya Dukung Wisata Pantai Gandoriah Pariaman Provinsi Sumatera Barat - Putri, Rista Ananda; Febriandi, Febriandi (Lembaga Yasin AlSys, 2025)
This study aims to identify existing facilities and assess the land carrying capacity in relation to tourist visits at Gandoriah Beach, Pariaman City. A mixed methods approach was employed, combining both quantitative and qualitative techniques. A total of 100 respondents were selected using accidental sampling. Qualitative data were collected through observation, interviews, and documentation, while quantitative data were obtained from questionnaires distributed to visitors. The findings reveal that: (1) The condition of amenities at Gandoriah Beach is categorized as very good based on facility assessments and observations; (2) The physical carrying capacity of the area indicates that the number of visitors has exceeded its sustainable limit, highlighting the need for intervention by relevant authorities to regulate and limit tourist numbers in order to maintain comfort and environmental sustainability; (3) Visitor satisfaction levels fall within the